2015
DOI: 10.1002/open.201500129
|View full text |Cite
|
Sign up to set email alerts
|

Expedient Synthesis of the Pentasaccharide Repeating Unit of the Polysaccharide O‐Antigen of Escherichia coli O11

Abstract: A convergent [3+2] block synthetic strategy was developed for the synthesis of the pentasaccharide repeating unit of the cell wall O‐antigen of Escherichia coli O11 strain in excellent yield in a minimum number of steps. Several suitably functionalized thioglycoside derivatives were used as glycosyl donors during the synthesis of the target compound. A thioglycoside was the glycosyl donor used to couple with another thioglycoside derivative in a highly stereoselective manner exploiting the difference of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Production processes for polysaccharides from natural sources suffer from difficulties in the extraction and purification of the product [24]. A further disadvantage lies in the batch-dependent variations in size and the related chain length of the polysaccharides [25]. A promising approach for the synthesis of polysaccharides with defined chain lengths is the cleavage of long-chain material through controlled enzymatic or thermal hydrolysis [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Production processes for polysaccharides from natural sources suffer from difficulties in the extraction and purification of the product [24]. A further disadvantage lies in the batch-dependent variations in size and the related chain length of the polysaccharides [25]. A promising approach for the synthesis of polysaccharides with defined chain lengths is the cleavage of long-chain material through controlled enzymatic or thermal hydrolysis [26,27].…”
Section: Introductionmentioning
confidence: 99%
“… 27 Initial attempts to glycosylate acceptors 15 and 16 in dichloromethane with 1.2 equivalents of thiophenyl fucoside 14 produced trisaccharides in alpha and beta mixtures. In contrast, stereospecific formation of trisaccharides was achieved when a mixed solvent of diethylether and dichloromethane (1 : 1) 50 , 51 was employed. The reaction of acceptors 15 and 16 with 1.2 equivalents of fucosyl donor 14 produced compounds 17 and 18 in 68% and 65% yields, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Another strategy has been to produce polysaccharides synthetically in blocks. The exact number can vary, such as a di-and tetra-saccharides (Budhadev & Mukhopadhyay, 2015), di-and tri-saccharides (Mandal, 2014;Mondal, Liao, Mondal, & Guo, 2015;Si & Misra, 2016), three disaccharides (Scott et al, 2016) and two tri-saccharides (Seeberger, Pereira, & Govindan, 2017). However, it should be noted that it is possible to compare assembly methods and one study revealed that linear assembly may be more effective than block assembly (Dhara & Misra, 2015;Seeberger et al, 2017).…”
Section: Polysaccharide Productionmentioning
confidence: 99%